Correction: Hydrophobic pillared square grids for selective removal of CO2 from simulated flue gas. Issue 94 (4th November 2015) - Elsaidi, Sameh K.; Mohamed, Mona H.; Schaef, Herbert T.; Kumar, Amrit; Lusi, Matteo; Pham, Tony; Forrest, Katherine A.; Space, Brian; Xu, Wenqian; Halder, Gregory J.; Liu, Jun; Zaworotko, Michael J.; et al.
Abstract : Correction for 'Hydrophobic pillared square grids for selective removal of CO2 from simulated flue gas' by Sameh K. Elsaidi et al., Chem. Commun., 2015, 51, 15530–15533.